2012
DOI: 10.1007/s00213-012-2883-x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of intramuscular ketamine and oral triazolam in healthy volunteers

Abstract: Rationale Several studies have documented impairments in memory processes as a result of ketamine administration; however, few studies have compared the profile of cognitive effects of ketamine to other drugs. Objectives The aim of this study was to compare the cognitive effects of ketamine with those of triazolam in healthy volunteers. Methods Doses of ketamine (0.2, 0.4 mg/kg intramuscular (i.m.)), triazolam (0.2, 0.4 mg/70 kg p.o.), and double-dummy placebos were administered to 20 volunteers under repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
4

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 36 publications
0
29
4
Order By: Relevance
“…These effects were consistent with previous studies of the NMDA antagonist ketamine. In previous studies, ketamine significantly decreased episodic word recall, word recognition, and working memory accuracy (Lofwall et al, 2006; Carter et al, submitted). Likewise, the profile of triazolam effects was also consistent with previous studies in that triazolam produced significant impairments in psychomotor and cognitive performance (Carter et al, 2009; Kleykamp et al, 2010; Mintzer and Griffiths, 2002; Reissig et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These effects were consistent with previous studies of the NMDA antagonist ketamine. In previous studies, ketamine significantly decreased episodic word recall, word recognition, and working memory accuracy (Lofwall et al, 2006; Carter et al, submitted). Likewise, the profile of triazolam effects was also consistent with previous studies in that triazolam produced significant impairments in psychomotor and cognitive performance (Carter et al, 2009; Kleykamp et al, 2010; Mintzer and Griffiths, 2002; Reissig et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
“…Thus, one of the aims of this study was to examine the acute dose effects of high doses of DXM on a variety of different cognitive measures. A second aim was to extend previous findings from our laboratory on the comparative pharmacology and the differential profiles of the cognitive effects of benzodiazepines such as triazolam (Carter et al, 2006, 2007, 2009; Mintzer and Griffiths 2002, 2005) and NMDA antagonists such as ketamine (Carter et al, submitted; Lofwall et al, 2006). On the basis of the results from these previous studies, we hypothesized that the effects of DXM on participants’ subjective ratings of drug effects and of their own cognitive performance impairment would be greater than those of triazolam, whereas the cognitive impairments observed after administration of triazolam would be greater than those observed after DXM.…”
Section: Introductionmentioning
confidence: 98%
“…so that f(π) = d satisfies the constraints in Equations (4) and (5). For the current study, either u = 0 or u = 2.…”
Section: Construction Of Population Modelsmentioning
confidence: 96%
“…For these studies, sample variance is an important issue. None of these studies reported CIs, three studies [5,6,8] reported standard errors, two studies [3,9] reported p-values pertaining to the null hypothesis γ = 0, and three studies [2,4,7] reported only the estimate.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation